2016
DOI: 10.1002/jez.2027
|View full text |Cite
|
Sign up to set email alerts
|

Frog Foam Nest Protein Diversity and Synthesis

Abstract: Some amphibian species have developed a breeding strategy in which they deposit their eggs in stable foam nests to protect their eggs and larvae. The frog foam nests are rich in proteins (ranaspumin), especially surfactant proteins, involved in the production of the foam nest. Despite the ecological importance of the foam nests for evolution and species conservation, the biochemical composition, the long-term stability and even the origin of the components are still not completely understood. Recently we showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…While the use of foam nest as reproductive strategy among anurans is well known in the literature (e.g. Tyler and Davies 1979;Hödl 1990Hödl , 1992Kadadevaru and Kanamaedi 2000;Bastos et al 2010;Cruz et al 2016), as well as some of the foams biotechnological applications (Hissa et al 2016;Cooper et al 2017), there are only few studies regarding morphometry and ambient variables associated with P. cuvieri nests (Bokermann 1962; Barreto and Andrade 1995;Andrade 2007). Our current observations of P. cuvieri building nests under herbaceous vegetation close to the studied pond, corroborates findings by Barreto and Andrade (1995) and Uetanabaro et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…While the use of foam nest as reproductive strategy among anurans is well known in the literature (e.g. Tyler and Davies 1979;Hödl 1990Hödl , 1992Kadadevaru and Kanamaedi 2000;Bastos et al 2010;Cruz et al 2016), as well as some of the foams biotechnological applications (Hissa et al 2016;Cooper et al 2017), there are only few studies regarding morphometry and ambient variables associated with P. cuvieri nests (Bokermann 1962; Barreto and Andrade 1995;Andrade 2007). Our current observations of P. cuvieri building nests under herbaceous vegetation close to the studied pond, corroborates findings by Barreto and Andrade (1995) and Uetanabaro et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they revealed that the foam nest from L. vastus contained more than 100 proteins. Among them, Lv-RSN-1 was about 45% of the total protein in the foam nest (Hissa et al, 2016). The Japanese green tree frog, Rhacophorus arboreus (Amphibia, Anura, Rhacophoidae), is a frog species that is endemic to Japan (Fig.…”
Section: Identification Of Novel Proteins In Foam Nests Of the Japanementioning
confidence: 99%
“…In anuran amphibians, foam nest construction is associated with adaptation to terrestrial life, and 10 out of the 41 different reproductive modes found in anurans involve foam nest construction [57]. Depending on the anuran species, the foam nests are produced in underground burrows, float on the water surface, or are even suspended from vegetation [4, 8–10]. Several functions have been identified for the production of anuran foam nests, such as protecting eggs and embryos against predators, desiccation, microbial degradation and thermal damage, as well as supplying oxygen and serving as a food source for tadpoles [2, 8, 11–13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on anuran foam nests have mostly focused on their structure and biochemical composition and the construction behavior leading to them [4, 13, 1517]. Well-studied foam-nesting species include frogs from the genus Leptodactylus , especially the túngara frog [4, 10, 12, 14, 15]. Hissa et al [16] and Fleming et al [17] reported that the foam nest components of Leptodactylus frogs were a mixture of proteins termed ranaspumins, with surfactant activity, cystatin activity and lectin composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation